Community trust and decisions in the conversion of agricultural land (Case study: Mulyoagung Village, Indonesia) - Rahmawati Rahmawati; Enock Siankwilimba; Abdul Wahid Hasyim; Gunawan Prayitno; I Nyoman Suluh Wijaya; Agus Dwi Wicaksono; Aris Subagiyo (Region : Jurnal Pembangunan Wilayah dan Perencanaan Partisipatif, 2024)
Urbanization is caused by a drastic increase in population in an area, thus spurring high demand for space or land, leading to land conversion. The phenomenon of land conversion in rural areas is a reciprocal relationship between urban and rural areas influencing the spread of urbanization to rural areas. Mulyoagung Village, one of the villages in Malang, experiencing significant agricultural land conversion. This research aims to identify the classification of area based on the land conversion. Discussion also made on the beliefs and the demographics that played a role in influencing decisions regarding land conversion. The result revealed that Mulyoagung Village is a secondary rural peri-urban classification located between Malang City and Batu City, experienced a conversion of 24.01% of non-built-up land to built-up land within a period of 20 years (2002-2022). The conversion led to a change from initially rural fringe to urban-rural fringe. This results also supported by SEM-PLS analysis which showed that community demographics are the central construct influencing the decision of farming communities to convert their agricultural land.